Test characteristics of urinary biomarkers depend on quantitation method in acute kidney injury - Md Ralib, Azrina; Pickering, John W.; Shaw, Geoffrey M.; Devarajah, Prasad; Edelstein, Charles L.; Bonventre, Joseph V.; Endre, Zoltan H. (American Society of Nephrology, 2012)
The concentration of urine influences the concentration of urinary biomarkers of AKI. Whether normalization to urinary creatinine concentration, as commonly performed to quantitate albuminuria, is the best method to account for variations in urinary biomarker concentration among patients in the intensive care unit is unknown. Here, we compared the diagnostic and prognostic performance of three methods of biomarker quantitation: absolute concentration, biomarker normalized to urinary creatinine concentration, and biomarker excretion rate. We measured urinary concentrations of alkaline phosphatase, gamma-glutamyl transpeptidase, cystatin C, neutrophil gelatinase–associated lipocalin, kidney injury molecule–1, and IL-18 in 528 patients on admission and after 12 and 24 hours. Absolute concentration best diagnosed AKI on admission, but normalized concentrations best predicted death, dialysis, or subsequent development of AKI. Excretion rate on admission did not diagnose or predict outcomes better than either absolute or normalized concentration. Estimated 24-hour biomarker excretion associated with AKI severity, and for neutrophil gelatinase–associated lipocalin and cystatin C, with poorer survival. In summary, normalization to urinary creatinine concentration improves the prediction of incipient AKI and outcome but provides no advantage in diagnosing established AKI. The ideal method for quantitating biomarkers of urinary AKI depends on the outcome of interest.